The in vitro antimicrobial activity of silicone oils used in ophthalmic surgery - Chrapek, Oldrich; Vecerova, Renata; Koukalova, Dagmar; Maresova, Klara; Jirkova, Barbora; Sin, Martin; Rehak, Jiri (Biomedical papers, 2012)
Background: The aim of the study was in vitro assessment and comparison of the antimicrobial activity of three types of silicone oils used in ophthalmic surgery.Methods: The silicone oils (Arciolane 1300 centistokes, Arciolane 5500 centistokes and Oxane Hd, heavy silicone oil) were inoculated with microbes common in endophthalmitis and their growth was observed continuously. Control tests of microbial growth were performed on silicone oil-free media, i.e. saline and standard enrichment media. In both tested oils and control media, the microbes were cultured aerobically for 21 days, bacteria at 37 °C and yeasts and fungi at 30 °C. Prior to and during incubation at given intervals (days 0, 2, 4, 7, 9, 11, 14, 16, 18 and 21), 10 μl samples were taken from all test tubes. These were diluted in saline in a series of test tubes, with the minimum concentration reaching 10-8. From each dilution, 25 μl were inoculated onto agar media. After 24 h of aerobic incubation at 37 °C (bacteria) and 48 h at 30 °C (yeasts and fungi), the grown colonies were counted and the numbers of colony-forming units in 1 ml (CFU/ml) were determined.Results: In vitro, the highest antimicrobial effect was observed for the Oxane Hd silicone oil.Conclusions: If endophthalmitis is treated by pars plana vitrectomy, the application of Oxane Hd silicone oil into the vitreous cavity at the end of surgery may contribute to the elimination of microorganisms from the intraocular space but clinical trials are needed to assess its safety.
Keywords: antimicrobial activity; endophthalmitis; silicone oil